The liability of online intermediaries under European Union law - Daria Bulgakova; Sintija Deruma (Kyiv-Mohyla Law and Politics Journal, 2023)
This research explores the complex and multifaceted issue of online intermediary liability. It illuminates the challenges arising from the absence of uniform regulations and the need for a collaborative system between online intermediaries and rightsholders. Specifically, the article scrutinizes the liability of online intermediaries under European Union law for violations of legal interests in online content. It strives to balance intermediary liability frameworks and fair competition, drawing attention to the relationship between specific provisions and the concurrent regime outlined in the e-Commerce Directive. Moreover, the article evaluates the consistency of liability frameworks for online intermediaries and their compliance with market functioning rules under the Trade Secrets and the Unfair Commercial Practices Directives. Furthermore, the article consults the consequences of the EU Directive on Copyright in the Digital Single Market, which holds online user-generated content platforms directly responsible for infringing content. And, unlike the original draft, the final version of this directive does not impose general monitoring obligations. Nevertheless, online intermediaries may need to implement filtering measures to avoid liability for unauthorized communication of copyright-protected works to the public. The writing also considers the impact of a prior legal framework, and the Digital Service Act established to address the issue of online intermediaries being held liable for any illegal information disseminated through their platforms. The research underscores the innovative features of the Digital Services Act, acknowledging the challenges of creating a practical legal framework striving to avoid conflicts with relevant laws. Therefore, this paper sheds light on the complex nature of online intermediary liability to the EU approach accordingly.